Pengaruh Penggunaan Alsintan Terhadap Pendapatan Petani (Studi Kasus di Kelompok Tani Barantas Kab. Sidenreng Rappang) - Nurdin, Romy; Yusriadi, Yusriadi; Sriwahyuningsih, A Erna (UNIVERSITAS NEGERI MAKASSAR, 2021)
The purpose of this study was to determine the impact of using alsintan on farmer’s income. This research is descriptive quantitative. The method of data retrieval used is observation, questionnaire and interview The data analysis technique used is multiple linear regression analysis. This multiple linear analysis technique is used to determine the effect of the independent variable on the dependent variable. The results show that there is a significant influence between management management (X1) on farmer income (Y), this is shown in the coefficient table with the equation equation value of 16,749 with a significance value of 0.000 so that the value is smaller than the alpha value (α), which is 0 , 05. This shows that good agricultural land management will have an effect on increasing farmers 'income, on the other hand, if agricultural land is not managed optimally, farmers' income will decrease.